THE IMPACT OF INSTITUTIONS ON ENTREPRENEURSHIP: A CASE OF VIETNAM - Trần Thanh Trúc; Trương Ngọc Hảo (Tạp chí Khoa học Đại học Đà Lạt)
This study attempts to examine the impact of institutional factors on entrepreneurship in Vietnam from 2005 to 2015. The study utilizes quantitative research methods with panel data collected from secondary sources of the General Statistics Office, Statistical Yearbook of Provinces, and the Provincial Competitiveness Index (PCI). The results based on fixed effects estimation show that the “entry cost” and “land access and stability in land use” are two indicators that have the strongest negative effect on entrepreneurship in Vietnam. Therefore, it is necessary to have specific policies to reduce the cost of market entry as well as more effective land use options to support entrepreneurship development in Vietnam.